A preoperative education intervention to reduce anxiety and improve recovery among Chinese cardiac patients: a randomised controlled trial - Guo, Ping (2012)
Background: Patients awaiting cardiac surgery typically experience physical and psychological stress. Although there is evidence that preoperative education can improve postoperative outcomes among general surgical patients, less is known about preoperative education for patients undergoing cardiac surgery, particularly in the context of healthcare delivered in China.